Accidental chemical poisoning: Cases recorded at Benghazi Children’s Hospital (2018-2022) (Journal of Medical Sciences, 2024)
Children are more exposed to chemical poisoning incidents due to their desire to explore and love to see things they have. The aim of the study is to identify cases of chemical poisoning recorded at Benghazi Children's Hospitalf rom January 2018 - December 2022 were used. The results showed the highest rate of drug poisoning (70.9%) in children. The lowest percentage of cannabis was (5.5%), and it included age groups under 5 years of age (64.2%), and most cases appeared in males. The highest cases of drug poisoning were recorded in the winter, followed by poisoning with phosphorus compounds in the autumn, while kerosene cases were recorded in summer season. Hospital records show that most of the poisoning cases have been treated, while 6 children died (4 kerosene and 2drug injections). we need to educate parents about ways to deal with these substances and keep them out of the reach of children.